Systematics of the family Carditidae (Bivalvia: Archiheterodonta) in the Cenozoic of Argentina - Pérez, Damián E.; Río, Claudia J. Del (Zootaxa, 2017)
The systematics of the Family Carditidae is currently poorly elucidated. This paper reviews the Eocene to Pleistocene carditids from Patagonia and Entre Ríos Province (Argentina). Twelve species are described and illustrated and the presence of the genera Cyclocardia Conrad, Pleuromeris Conrad, Scalaricardita Sacco, Fasciculicardia Maxwell and Purpurocardia Maxwell in southern South America is discussed. The genus Scalaricardita is documented for the first time in South America. Two new genera, Darwinicardia gen. nov. and Kolmeris n. gen. are proposed for the species ‘Venericardia’ patagonica (Sowerby) and ‘V.’ tehuelchana (Ihering), respectively, and one new species, Cyclocardia dalek sp. nov., is described.